FENOMENA KEDUDUKAN HUKUM ANAK ZINA - Tutut Sartika Siregar; Khairil Anwar (Jurnal Syaikh Mudo Madlawan: Kajian Ilmu-Ilmu Keislaman, 2025)
Marriage in Islam has noble purposes and wisdom, including creating peace of mind for husband and wife, personal maturity for both, and the birth of a quality generation. Discussions on marriage in the millennial era often encounter new problems, such as the emergence of the term "married by accident" (MBA), more commonly known as a marriage that occurs due to a prior pregnancy. The legal phenomenon regarding the status of children born of adultery is a complex issue and requires in-depth discussion from various perspectives. Statistically, cases of adultery in Indonesia show a significant number, although accurate data is difficult to obtain due to its sensitive nature. Many children born of adultery subsequently face problems regarding their legal status and rights. Furthermore, it also has social and psychological impacts. Children of adultery often face negative social stigma. In some communities, they may receive different treatment than other children born of legal marriage. This can affect their psychological and social development. This is related to various applicable legal provisions, both within the context of state law and Islamic law.